Impact of Puroindolines on Semisweet Biscuit Quality: A Fractionation–Reconstitution Approach. Issue 6 (20th November 2013) - Pauly, Anneleen; Pareyt, Bram; Lambrecht, Marlies A.; Fierens, Ellen; Delcour, Jan A.
ABSTRACT: Puroindoline (PIN) proteins are a factor determining wheat kernel endosperm texture. Biscuits are preferably made from flour from soft wheat ( Triticum aestivum L.). Such wheat contains relatively high levels of wild‐type PINs, the impact of which on biscuit quality is unclear. We here studied the impact of PINs on biscuit texture using model flour samples reconstituted from starch and gluten fractions with varying PIN levels. These were obtained by fractionating flour from soft or durum wheat containing either wild‐type or no PINs, respectively. This approach allowed largely retaining the interaction between PINs and either starch or gluten, such as it exists in flour. High PIN levels enhanced air incorporation during dough preparation, increased dough (lateral) expansion, and yielded larger biscuits with higher porosity, which was mainly because of the larger pores. Biscuit fracture stress negatively correlated with PIN level. Porosity contributed to biscuit mechanical properties, but PINs also affected biscuit matrix strength, which in turn affected fracture stress. PINs seem to exert their softening effect when present above a threshold level, and then they have a stronger impact on biscuit fracture stress than the wheat endogenous lipids.